A review of telavancin activity in in vitro biofilms and animal models of biofilm-associated infections. (August 2015) - Chan, Cynthia; Hardin, Thomas C; Smart, Jennifer I
ABSTRACT : Tissue- and device-associated biofilm infections are important medical problems. These infections are difficult to treat due to a high-level of tolerance to antibiotics. Telavancin has been studied in several in vitro biofilm models and has demonstrated efficacy against staphylococcal and enterococcal-associated biofilm infections, including those formed by methicillin-resistant Staphylococcus aureus . Telavancin was effective against the difficult-to-treat vancomycin- and glycopeptide-intermediate strains of S. aureus in these models. Furthermore, the efficacy of telavancin has been evaluated in several biofilm-related in vivo models, including osteomyelitis, endocarditis and device-associated infections in rabbits. Overall, telavancin exhibited similar or greater efficacy than vancomycin and other comparators in these animal models and maintained activity against vancomycin-intermediate and daptomycin nonsusceptible strains of S. aureus .